Hijab and Mantilla in the Qur'an and the Bible: Comparative Study - Nur Alif, Muhamad; Masruchin, Masruchin; Hendro, Beko (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
Hijab (veil) was seen by the general public as a product of Islam and Arab culture, but looking back at history, as recorded in the book of bilarama (3000), hijab (veil) was a product of human civilization it can be seen that it is a cultural product. The role of religion in the process of the journey (veil) of hijab is acculturation, establishing different kinds of rules to create perfection in hijab itself. The focus of this study is to analyze the two holy books of god's religion (Al-Qur'an and the Bible) through their teachings and historical aspects to clear up misconceptions about prejudice among the common people, and to get to know the people, that's it and through our commonalities and differences, we become more tolerant. This study is based on the qualitative foundations of library research style, and the research focus is on comparative research. The important point in this text is that hijab is not a product of religion, but the result of culture and religion setting rules. The Bible and Qur'an require secrecy, Muslim women wear hijab during daily activities, but Catholic women are not required by canon law to wear mantillas during religious events or prayers, the mantilla is not compulsory under canonic law, and the hijab is compulsory under Islamic law.